Approaches to Translating Dialogical Unity with Tag Questions in Shakespeare’s Tragedy “Hamlet” - N. Yu. Merkuryeva (Научный диалог, 2025)
This article explores the approaches to translating dialogical unity featuring tag questions from William Shakespeare’s tragedy “Hamlet.” It analyzes translations of a specific fragment of the source text, which contains this dialogical unity, carried out by various domestic translators including N. Polev, A. Kroneberg, M. Vronchenko, and M. Zagulaev in the 19th century, as well as B. Pasternak, M. Lozinsky, A. Radlova, and Y. Lifshitz in the 20th century, and A. Agroskin, I. Peshkov, A. Chernov, and V. Poplavsky in the 21st century. The study highlights the diversity of translation options and characterizes the differences in the choice of translation techniques. It demonstrates that the variability of translations is linked to the translator’s attitude towards tag questions. Two directions of interpretation by translators are identified: when understood as interrogative sentences, the tags are rendered as brief question structures such as “isn't it?”, “right?”, “isn't that so?”, “perhaps?”, “why not?”, which can also be more elaborate: “could it really be so?”, “it could have been that way too, couldn't it?” Conversely, if tag questions are interpreted as emotionally charged statements by the character, translators often see no need to convey the interrogative tags. The analysis reveals that the interpretation of lines containing tag questions depends on the translators’ perception of Shakespeare’s intent and their understanding of the mood and state of the characters.